Management and Outcome in Patients with Advanced Juvenile Nasopharyngeal Angiofibroma - Rupa, Vedantam; Mani, Sunithi Elizabeth; Backianathan, Selvamani; Rajshekhar, Vedantam (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objective To report the management outcome in a series of patients with advanced juvenile nasopharyngeal angiofibroma (JNA).Design Retrospective study.Setting Tertiary care teaching hospital.Participants Forty-five patients classified as Radkowski stage IIIA or IIIB who presented to us over the past 10 years.Main Outcome Measures Surgical approaches used and disease free outcomes in patients with advanced JNA.Results Surgical access for the extracranial component included open (41.9%) and expanded endonasal approaches (58.1%). Craniotomy (16.3%), endoscopy-assisted open approach (7%), or expanded endonasal approach (20.9%) was performed to excise the skull base or intracranial component. Follow up ranged from 4 to 96 months (mean, 20.3 months). Of 35 patients who underwent imaging at the first postoperative follow up, 25 (71.4%) had negative scans. Three symptomatic patients with residual disease underwent endoscopic excision and had negative scans thereafter. Of two others who had radiation therapy, one was disease free and the other lost to follow up. Five others had stable, residual disease. Three patients (8.6%) with recurrent disease underwent surgical excision, of whom two had minimal, stable residual disease. At the last follow-up, 27 (77.1%) patients had negative scans, and 7 (20%) had stable residual disease with one (2.9%) patient lost to follow-up.Conclusions Advanced JNA may be successfully treated in most cases with expanded endonasal/endoscopy assisted ± craniotomy approach after appropriate preoperative evaluation. At follow-up, only symptomatic patients or those with enlarging residue require treatment; periodic imaging surveillance is adequate for those with stable disease.
Keywords: angiofibroma; management; endoscopy; nasopharynx